Comparative study of peroxide oxidants activated by nZVI: Removal of 1,4-Dioxane and arsenic(III) in contaminated waters - Kang, Yu-Gyeong; Yoon, Hakwon; Lee, Woojin; Kim, Eun-ju; Chang, Yoon-Seok (ELSEVIER SCIENCE SA, 2018)
In this study, we investigated the performance of nanoscale zerovalent iron (nZVI) in the presence of the common oxidants, persulfate (PS), peroxymonosulfate (PMS) and hydrogen peroxide (HP), for the removal of 1,4-dioxane (1,4-D) and As(III) in contaminated waters. PS/nZVI showed the highest removal of both 1,4-D and As(III), followed by HP/nZVI and PMS/nZVI in order. The removal increased as the oxidant dosage increased, whereas only As(III) removal was enhanced with increasing nZVI dosage. The maximum removal occurred at pH 3 and only PS/nZVI could remove As(III) as the pH increased from 3 to 7. Radicals such as center dot OH and SO4 center dot- were produced from the oxidant/nZVI system and the radicals contributed more to the removal of 1,4-D than As(III). The removal of As species was significantly influenced by nZVI dissolution, which consequently caused adsorption and co-precipitation as the main removal mechanisms. For environmental applications, the PS/nZVI system efficiently treated a real groundwater contaminated by 1,4-D and As(III), respectively. The basic knowledge gained from this study could help in selecting a proper oxidant to use with nZVI to purify surface and groundwaters contaminated by organic and inorganic contaminants at the same time.
Keywords: ZERO-VALENT-IRON; HYDROGEN-PEROXIDE; PERSULFATE OXIDATION; AQUEOUS-SOLUTION; DEGRADATION; PEROXYMONOSULFATE; MECHANISM; ARSENITE; PH; DECOMPOSITION